Four millennia of geomorphic change and human settlement in the lower Usumacinta–Grijalva River Basin, Mexico. (April 2023) - Muñoz-Salinas, Esperanza; Cook, Duncan; Castillo, Miguel; Beach, Timothy; Luzzadder-Beach, Sheryl
The lower Usumacinta–Grijalva River Basin contains one of the richest biodiversity landscapes of the Maya region. Our research is based on (1) an integrative literature review of the geomorphological and archaeological papers published about the lower Usumacinta–Grijalva River Basin and (2) topographic analysis of digital elevation models using a geographical information system to explore the relationship between past human settlement and landscape accessibility along the coastal plain of Tabasco. This work provides a new synthesis of previous research and proposes new models for the geomorphic evolution of the lower Usumacinta–Grijalva River Basin in the context of four millennia of human land use and settlement. For the evolution of the strand-plain of the Usumacinta and Grijalva rivers, there are two published geochronological models that provide different chronologies. We discuss here how both geochronological models encompass Pre-Columbian human settlement in the delta. Interestingly, we notice that one of them overlaps a possible high-magnitude flood event (or events) that drove large geomorphic change around 750 CE (1200 BP), with implications for settlement patterns and chronology. Based on topographical analysis of the eastern-distal sector of the Usumacinta–Grijalva delta, we propose a new model for the evolution of this area with implications for the human occupation during the Mesoamerican Terminal Classic and Early Postclassic on the delta. As one of the main conclusions, we propose that the Pom–Atasta water bodies predate much of the Usumacinta–Grijalva delta and the most recent phase of delta building overlays the original lagoon barriers, resulting in a geomorphic setting more attractive to local human occupation after the Terminal Classic period. According to one of the geochronological models of the delta, this dates to ca. 900 CE, preceding the establishment of nearby settlements such as Atasta.